Stock Market Liquidity in Chile - Brandao Marques, Luis (IMF Working Papers; Working Paper ;, 2016)
Chile has a large but relatively illiquid stock market. Global factors such as global risk appetite and monetary policy in advanced economies are key cyclical determinants of liquidity in Chilean equities. Evidence from a cross-section of emerging markets suggests strong protection of minority shareholders can help improve stock market liquitidity. Currently, illiquid in Chilean may have to pay 3 1/2 percent more as cost of equity. Corporate governance should be improved, namely through the adoption of a stewardship code.